2018
DOI: 10.1016/j.jaip.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical Differences of Childhood- and Adult-Onset Atopic Dermatitis

Abstract: Self-reported adult-onset AD is common and has distinct phenotypes with lesional predilection for the hands and/or head/neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 26 publications
7
82
6
2
Order By: Relevance
“…[1][2][3] AD usually first manifests in early infancy and childhood. 4,5 For about half of pediatric patients, however, AD persists into adulthood, 6,7 becoming a chronic, lifelong condition, 5 especially for patients with later-onset disease, or presenting with greater severity, or both. 8 AD can also initially appear in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] AD usually first manifests in early infancy and childhood. 4,5 For about half of pediatric patients, however, AD persists into adulthood, 6,7 becoming a chronic, lifelong condition, 5 especially for patients with later-onset disease, or presenting with greater severity, or both. 8 AD can also initially appear in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…8 AD can also initially appear in adulthood. 7,[9][10][11] AD prevalence in adults varies according to severity, assessment method, and region. Limited AD prevalence data in European adults indicate prevalence rates between 4.4% and 7.1% (with a range between countries of 2.2%e17.6%) 12,13 and trends of increasing prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis is a heterogeneous disorder with variable lesional morphology (eg, erythema, lichenification, erosions, scaling, oozing/weeping, prurigo nodules), 6 distribution (eg, extent, head and neck, hands and feet 7 ), age of onset, 8,9 persistence, 10 symptoms (eg, itch, skin pain, 11 sleep disturbance 12e14 ). A recent global systematic review and meta-analysis of AD characteristics identified 78 different signs and symptoms of AD, with significant variability by global region and patient age.…”
Section: Burden Of Admentioning
confidence: 99%
“…Atopic dermatitis (AD) is a common inflammatory skin condition that normally begins in early childhood and resolves before adolescence in up to 80% of cases . Two classes of persistent AD, that is early‐onset‐persistent and early‐onset‐late‐resolving, are both associated with filaggrin gene mutations, an increased AD genetic risk score, and a personal or parental history of atopy …”
Section: Introductionmentioning
confidence: 99%
“…1 Two classes of persistent AD, that is earlyonset-persistent and early-onset-late-resolving, are both associated with filaggrin gene mutations, an increased AD genetic risk score, and a personal or parental history of atopy. 2 A meta-analysis showed that about 20% of AD children experience persistent disease after 8 years, but only 5% after 20 years. 3 Recent studies confirm that it is difficult to study AD persistence properly since the disease is heterogeneous and recurrent.…”
Section: Introductionmentioning
confidence: 99%